The Effect of School Infrastructure Quality and Economic Factors on Academic Achievement of High School Students in East Java - Farid, Muhammad Miftah; Setiawan, Deddy; Solichin, M. Riadhos; Noviana, Naning Eko; Mustika Sari , Vina Budiarti (Westscience Press, 2024)
This research investigates the impact of school infrastructure quality and economic factors on the academic achievement of high school students in Central Java through a survey-based quantitative analysis. A diverse sample of 200 participants, including students, teachers, and parents/guardians, provided insights into demographic characteristics, perceptions of school infrastructure, economic conditions, and academic performance. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was employed to analyze the data. Results indicate positive perceptions of classrooms and laboratories, moderate economic conditions, and varied academic achievements within the sample. The measurement model confirmed the validity and reliability of constructs, while the structural model revealed significant positive relationships between school infrastructure quality, economic factors, and academic achievement. The findings have implications for educational policies, emphasizing the importance of targeted interventions to enhance the overall educational experience in East Java.